APAKAH ONDEL-ONDEL SEBAGAI WARISAN KEBUDAYAAN DALAM PERLINDUNGAN HUKUM KEKAYAAN INTELEKTUAL KOMUNAL ? - Liza Marina; Fahririn Fahririn; Bramandaru Kurniawan (Jurnal Hukum Mimbar Justitia, 2023)
Ondel-Ondel is a cultural heritage that is used as a complement to various traditional ceremonies and art activities that are performing, introducing Betawi culture or art performances but at this time there is a diversion of the function of ondel-ondel art which should be an Intangible Cultural Heritage, turning into a tool for busking, begging is considered a form of violation of public order. This study aims to analyze the protection of Betawi people's rights to Ondel-Ondel art as communal intellectual property whose use by the State and examine the application of legal protection for changes in the function of Ondel-Ondel art for busking by the DKI Jakarta government. This research uses normative juridical research. The protection of the Betawi people's rights to the art of Ondel-Ondel as Communal Intellectual Property, Traditional Cultural Expressions, by the state is still unclear and needs an explanation of the rules for the application of the state as a holder and who protects EBT and needs to involve indigenous peoples, as holders of EBT, in order to protect the ownership of Communal Property and concrete actions of the State in collaboration with the local community, public awareness, supervision and provide strict sanctions against violations of public order. Keywords: Ondel-ondel; Order; Communal.